¿Sobredosis de regulación? Algunos apuntes sobre la regulación farmacéutica - Vivanco Vargas, Carolina (2020)
The following article analyzes pharmaceutical regulations from the point of view of the qualifications that necessary to operate in said industry. It also analyzes the current situation of the pharmaceutical sector, according to various studies. Additionally, it identifies some prerequisites required for the operation of pharmacies and drugstores that constitute obstacles for the proper development of said pharmaceutical establishments, commenting thus on the resolutions issued by INDECOPI on the particular.